Laparoscopic retrieval of displaced copper T: Two case reports - Bajracharya, Anu; Shah, Rachana (Journal of Kathmandu Medical College, 2014)
Intrauterine contraceptive device (IUCD) is a widely accepted contraceptive method because of its safety, economic quality, efficiency and reversibility. However, it may cause serious complications like bleeding, uterine perforation and migration to abdominopelvic cavity with perforation or adhesion to adjacent organs or omentum. We report two cases of uterine perforation with copper T insertion that were displaced in the pelvic cavity. In both the cases, IUCD was located by using plain X-rays of abdomen, ultrasonography, and hysteroscopy and finally laparoscopy was performed to identify the location and then remove the IUCD. DOI: http://dx.doi.org/10.3126/jkmc.v3i1.10923 Journal of Kathmandu Medical College Vol. 3, No. 1, Issue 7, Jan.-Mar., 2014, Page: 38-40